Genotype AA of ACE2 G8790A (rs2285666) Has Protective Potential Against COVID-19 Disease Severity - Chukkayapalli, Sowmya Gayatri; Suravaram, Swati; Reddy, Bharat Kumar; Siddiqui, Imran Ahmed (Molecular and Cellular Biomedical Sciences, 2023)
Background: SARS-CoV-2 virus uses angiotensin converting enzyme 2 (ACE2), a key enzyme of the renin angiotensin system (RAS) as the functional receptor for cell fusion and induction of infections in the respiratory system. Functional ACE2 gene polymorphisms may lead to RAS imbalance and are associated with COVID-19 susceptibility and severity. ACE2 G8790A (rs2285666), a splice region variant, is well characterized in various populations across the world. In the present study, the role of ACE2 G8790A (rs2285666) variant as risk predictor for severity of COVID-19 infection was investigated.Materials and methods: One-hundred COVID-19 subjects were included in the study and divided into: subjects with a history of severe infection and ICU-admitted (Group 1) and subjects with mild to moderate COVID-19 infection (Group 2). Genotype analysis for rs2285666 of ACE2 was performed using polymerase chain reaction and restriction fragment length polymorphism (PCR-RFLP) method.Results: The distribution of ACE2 G8790A (rs2285666) genotypes were GG 62%, GA 18%, and AA 20% in Group 1 and GG 34%, GA 14%, and AA 52% in Group 2, respectively. The A allele of rs2285666 (p≤0.001; OR=3.4; 95% CI=1.89–6.107) were less frequent in Group 1 as compared to Group 2. Also, a statistically significant difference was found between severity of COVID-19 infection with age and comorbidities such as diabetes, hypertension, chronic kidney disease, but not gender.Conclusion: Our findings suggest the possibility of a protective mechanism of the AA genotype of ACE2 G8790A (rs2285666) variant against COVID-19 disease severity.Keywords: COVID-19, ACE2 gene, renin-angiotensin system, genetic association, rs2285666, sanger sequencing